Glair glands and spawning in unmated crayfish: a comparison between gonochoristic slough crayfish and parthenogenetic marbled crayfish - Vogt, Günter (Invertebrate zoology, 2018)
In the period before spawning, freshwater crayfish females develop glair glands on the underside of the pleon. These glands produce the mucus for a gelatinous tentlike structure in which the eggs are fertilized and attached to the pleopods. Long-term observation of females of the sexually reproducing slough crayfish, Procambarus fallax, kept in captivity revealed that the glair glands developed in late winter and late summer of each year independently of the presence of males. In mated females, they secreted their contents shortly before spawning. In contrast, unmated females of slough crayfish did neither empty their glair glands nor spawn. Their glands persisted for an unusually long period of time and disappeared only during the next moult. Apparently, slough crayfish females use information on sperm availability to either spawn or save the resources. Females of marbled crayfish, Procambarus virginalis, a parthenogenetic all-female descendant of slough crayfish, developed glair glands in approximately the same periods of the year but generally spawned despite of the lack of males. These findings suggest that in marbled crayfish glair secretion and spawning is decoupled from mating. Therefore, the species pair P. fallax and P. virginalis seems to be particularly suitable to investigate the regulation of spawning in freshwater crayfish.